Nursery pig performance in response to meal and pelleted diets fed with irradiated or non-irradiated spray-dried animal plasma - C N Groesbeck; J Bergstrom; C R Neill; K R Brown; N Z Frantz; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
A 25-d trial was conducted to determine the effects of feeding meal and pelleted diets, with or without irradiated spray-dried animal plasma (SDAP; AP 920), on the growth performance in nursery pigs. A total of 192 pigs (initially 13.2 ± 1.9 lb and 21 ± 3 d of age) were used, with 6 pigs per pen and 6 pens per treatment. Pigs were randomly allotted in a 2 × 2 factorial to pens, blocked by weight, and randomly allotted to one of four dietary treatments. The main effects were diet form, meal or pellet, and either irradiated SDAP or nonirradiated SDAP. The experimental treatments consisted of a single diet that was fed in either meal or pelleted form, with or without irradiation of SDAP for Phase 1 (d 0 to 11), and a common diet for Phase 2 (d 11 to 25). Pig fed pelleted diets from d 0 to 3 had a greater ADG, ADFI, and improved F/G (P<0.03) than did pigs fed meal diets. Irradiation of SDAP had no effect on performance from d 0 to 3; for d 3 to 11, however, there was a diet form × SDAP irradiation interaction (P<0.01), and for d 0 to 11 there was interaction for ADG and F/G (P<0.07). Pigs fed irradiated SDAP in meal form had similar growth performance to those fed pelleted treatments. For producers that manufacture their own Phase 1 diet in meal form, use of irradiated SDAP can result in performance equal to that of nursery pigs fed a pelleted diet.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Nursery pig; Meal; Pellet; Spray-dried animal plasma; Irradiation; Swine